Biomedical materials and diagnostic devices - Tiwari, Ashutosh, 1945- (Hoboken, N.J. : John Wiley & Sons, 2012)
'The functional materials with the most promising outlook have the ability to precisely adjust the biological phenomenon in a controlled mode. Engineering of advanced bio- materials has found striking applications in used for biomedical and diagnostic device applications, such as cell separation, stem-cell, drug delivery, hyperthermia, automated DNA extraction, gene targeting, resonance imaging, biosensors, tissue engineering and organ regeneration'--Provided by publisher.
Application of the collagen as biomaterials / Kwangwoo Nam and Akio Kishida -- Biological and medical significance of nanodimensional and nanocrystalline calcium orthophosphates / Sergey V. Dorozhkin -- Layer-by-layer (LbL) thin film : from conventional to advanced biomedical and bioanalytical applications / Wing Cheung -- Polycaprolactone based nanobiomaterials / Narendra K. Singh and Pralay Maiti -- Bone substitute materials in trauma and orthopedic surgery properties and use in clinic / Esther M.M. Van Lieshout -- Surface functionalized hydrogel nanoparticles / Mehrdad Hamidi, Hajar Ashrafi, and Amir Azadi -- Utility and potential application of nanomaterials in medicine / Ravindra P. Singh ... [et al.] -- Gold nanoparticle-based electrochemical biosensors for medical applications / Ulku Anik -- Impedimetric DNA sensing employing nanomaterials / Manel del Valle and Alessandra Bonanni -- Bionanocomposite matrices in electrochemical biosensors / Ashutosh Tiwari, Atul Tiwari -- Biosilica-nonocomposites-nanobiomaterials for biomedical engineering and sensing applications / Nikos Chaniotakis, Raluca Buiculescu -- Molecularly imprinted nanomaterial-based highly sensitive and selective medical devices / Bhim Bali Prasad and Mahavir Prasad Tiwari -- Immunosensors for diagnosis of cardiac injury / Swapneel R. Deshpande ... [et al.] -- Ground-breaking changes in mimetic and novel nanostructured composites for intelligent-, adaptive-, and in vivo-responsive drug delivery therapies / Dipak K. Sarker -- Progress of nanobiomaterials for theranostic systems / Dipendra Gyawali ... [et al.] -- Intelligent drug delivery systems for cancer therapy / Mousa Jafari ... [et al.] -- The evolution of abdominal wall reconstruction and the role of nonobiotecnology in the development of intelligent abdominal wall mesh / Cherif Boutros, Hany F. Sobhi, and Nader Hanna -- Poly(polyol sebacate)-based elastomeric nanobiomaterials for soft tissue engineering / Qizhi Chen -- Electrospun nanomatrix for tissue regeneration / Debasish Mondal and Ashutosh Tiwari -- Conducting polymer composites for tissue engineering scaffolds / Yashpal Sharma, Ashutosh Tiwari, and Hisatoshi Kobayashi -- Cell patterning technologies for tissue engineering / Azadeh Seidi and Murugan Ramalingam.
Includes bibliographical references and index.
Keywords: Tissue Engineering; Biomedical materials; Diagnostic imaging; Nanotechnology